Analisis Tingkat Kepuasan Pengunjung Terhadap Fasilitas di Ekowisata Mangrove Wonorejo Surabaya (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The Wonorejo Mangrove Ecotourism Site in Surabaya faces challenges in sustaining visitor loyalty amid high tourist visitation. This study aims to analyze the effect of ecotourism facilities on visitor satisfaction and to determine the extent of their contribution. A quantitative approach with a causal correlational design using simple linear regression analysis was applied. The study involved 100 respondents selected through accidental sampling. The analysis results show a regression equation of Y = -3.114 + 0.418X with a t-statistic value of 53.964 and a significance value of 0.000 (less than 0.05). These findings prove that ecotourism facilities have a positive and significant effect on visitor satisfaction. Furthermore, an R-squared value of 0.967 indicates that 96.7% of visitor satisfaction is determined by the facility factor, while the remaining 3.3% is explained by other variables outside the model. The high coefficient of determination reflects a strong homogeneity of experience among visitors when interacting with the physical attributes of the destination. Based on these results, the management is recommended to continuously maintain and optimize the quality of physical infrastructure as a core tangible element to maintain positive confirmation, maximize visitor satisfaction, and encourage repeat visitation in this urban conservation area. .